The Impact of Cultural Differences and Religion on Television Advertising - Dagher, Grace (2004)
The purpose of this study is to compare television advertisements in several Arab countries (Saudi Arabia, Egypt, and Lebanon) and the United States. We fulfill this objective by conducting a television advertisement content analysis. We find similarities and differences between Arab and U.S. advertising.